Comparison of the therapeutic effects of mesenchymal stem cells derived from human dental pulp (DP), adipose tissue (AD), placental amniotic membrane (PM), and umbilical cord (UC) on postmenopausal osteoporosis - Li, Chuncai; Liu, Yincong; Deng, Mingxing; Li, Jun; Li, Shengqi; Li, Xiaoyu; Zuo, Yuling; Shen, Chongyang; Wang, Yichao (Frontiers in Pharmacology, 2024)
Background: Osteoporosis is a systemic bone disease characterized by bone loss and microstructural degeneration. Recent preclinical and clinical trials have further demonstrated that the transplantation of mesenchymal stem cells (MSCs) derived from human adipose tissue (AD), dental pulp (DP), placental amniotic membrane (AM), and umbilical cord (UC) tissues can serve as an effective form of cell therapy for osteoporosis. However, MSC-mediated osteoimmunology and the ability of these cells to regulate osteoclast-osteoblast differentiation varies markedly among different types of MSCs. Methods: In this study, we investigated whether transplanted allogeneic MSCs derived from AD, DP, AM, and UC tissues were able to prevent osteoporosis in an ovariectomy (OVX)-induced mouse model of osteoporosis. The homing and immunomodulatory ability of these cells as well as their effects on osteoblastogenesis and the maintenance of bone formation were compared for four types of MSCs to determine the ideal source of MSCs for the cell therapy-based treatment of OVXinduced osteoporosis. The bone formation and bone resorption ability of these four types of MSCs were analyzed using micro-computed tomography analyses and histological staining. In addition, cytokine array-based analyses of serological markers and bioluminescence imaging assays were employed to evaluate cell survival and homing efficiency. Immune regulation was determined by flow cytometer assay to reflect the mechanisms of osteoporosis treatment. Conclusions: These analyses demonstrated that MSCs isolated from different tissues have the capacity to treat osteoporosis when transplanted in vivo. Importantly, DP-MSCs infusion was able to maintain trabecular bone mass more efficiently with corresponding improvements in trabecular bone volume, mineral density, number, and separation. Among the tested MSC types, DP-MSCs were also found to exhibit greater immunoregulatory capabilities, regulating the Th17/Treg and M1/M2 ratios. These data thus suggest that DP-MSCs may represent an effective tool for the treatment of osteoporosis.